Emodin inhibits bladder inflammation and fibrosis in mice with interstitial cystitis by regulating JMJD3 - Junyu Lai; Xing Liu; Hongwei Su; Yongsheng Zhu; Ke Xin; Mingwei Huang; Songtao Luo; Hai Tang (Acta Cirúrgica Brasileira, 2023)
ABSTRACT Purpose: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a devastating urological chronic pelvic pain condition. In search of a potential treatment, we investigated the effect of emodin on IC/BPS inflammation and fibrosis, and explore the potential mechanism. Methods: An experimental model of interstitial cystitis was induced by cyclophosphamide, and human bladder smooth muscle cells were treated with lipopolysaccharide to establish the cell model in vitro. In both models, inflammation- and fibrosis-related indexes were measured after emodin administration. Furthermore, the specific antagonists were used to dig for the mechanisms underlying the response to emodin treatment. Results: Emodin significantly ameliorated management of cystitis, reduced the amount of inflammatory cytokines (tumor necrosis factor-α, monocyte chemoattractant protein-1, interleukin-1β, interleukin-8, and interleukin-6) in models, as well as reducing the synthesis of fibrosis marker including collagen1, collagen3, vimentin, fibronectin and α-smooth muscle actin. Further mechanism studies demonstrated that emodin inhibited inflammatory reaction and fibrosis through blocking lysine-specific demethylase 6B (JMJD3) expression via JAK/STAT, NF-κB and TGF-β/SMAD pathways. Conclusions: Our study reveals the critical role of emodin-JMJD3 signaling in interstitial cystitis by regulating inflammation, fibrosis, and extracellular matrix deposition in cells and tissues, and these findings provide an avenue for effective treatment of patients with cystitis.